Scheduling algorithms for fault-tolerance in hard-real-time systems - Bertossi, Alan A.; Mancini, Luigi V. (1991)
Abstract: "Many time-critical applications require high performance even if the system can suffer failures. This paper considers a distributed system with periodic tasks which can checkpoint their state on some reliable medium in order to handle failures. The problem of preemptive scheduling a set of such tasks is discussed where every occurrence of a task has to be completely executed before the next occurrence of the same task. A new class of scheduling algorithms is proposed which is based on a uniform rate strategy. This strategy yields optimal schedules in the absence of failures, and sub-optimal schedules when failures do occur. The performance of the solutions proposed is evaluated in terms of the number of processors and the number of preemptions needed
Keywords: Fault-tolerant computing; Real-time data processing